Sensitivity analysis in linear programming adds new variables and new constraints at the same time - عواد كاظم شعلان (Iraqi Journal for Administrative Sciences, 2024)
Sensitivity analysis is considered the most important link in the subject of linear programming and is concerned with determining the ranges within which the basis (basis) of the optimal solution table remains unchanged for each of the following cases: change in capabilities or available resources (limits of constraints change coefficients of the objective function, profits or losses), change in technical coefficients, coefficients of variables In constraints, add new variables, add new constraints)!. These topics were not discussed together, while the studies discussed the topic of changes in the objective function parameters and changes in the limits of constraints at the same time.